Early Cretaceous Aptian charcoal from Xinchang Petrified Wood National Geopark of Zhejiang province, eastern South China - Zhang, F.; Chen, H.; Batt, G.; Li, Zheng-Xiang; Yang, S. (SEPM, 2014)
We report on the distribution and character of fossil charcoal found in the Lower Cretaceous Guantou Formation in the Xinchang Petrified Wood National Geopark, eastern South China. All charcoal fragments studied so far exhibit well-preserved anatomical features of Araucarioxylon, consistent with the taxonomic classification assigned to this geopark’s widely known silicified tree trunks. Homogenized cell walls and high vitrinite reflectance values of charcoal particles, and the synchronous presence of tuffaceous deposits within the associated sequence, suggest that charcoal in the Xinchang Geopark may have mainly formed under conditions of complete exclusion of air by entombment in hot pyroclastic flows. Scattered charcoal fragments in several sandstone beds overlying the lahar sediments and locally high concentrations of fragments on channel-scoured surfaces are consistent with postformation reworking and transport of charcoal material.Zircon U–Pb SHRIMP dating of the volcanic interbeds of the Guantou Formation and underlying units define an age of Early Cretaceous (Aptian) for the charcoal. Both the fossil charcoal and associated petrified wood within the Guantou Formation may have an intimate genetic relationship with synchronous volcanism in the Xinchang Basin, eastern South China.